Image Guided Ablations for Thyroid Tumours - Nicosia Luca; Ferrari Federica; Mauri Giovanni; Orsi Franco (Journal of Thyroid Cancer, 2019)
Image guided ablations might be regarded as a promising effective and safe alternative for treatment of recurrent thyroid cancer in particular in patients with high surgical risk or refusing surgery. Furthermore, image guided ablations seems to represent a promising alternative to surgery or observation for micropapillary thyroid carcinoma, with the aim of providing an effective treatment with minimal invasiveness. Further studies are necessary to confirm the role in this setting
Keywords: thyroid